Mortality of frail elderly people living at home in relation to housing conditions. - Zhao, L (1993)
STUDY OBJECTIVE--The study was undertaken to identify any relationship between the mortality of frail elderly people living at home and their housing conditions. DESIGN AND SETTING--A cohort of frail elderly people living in Yao City, Osaka Prefecture, Japan was followed for six years. Data on demographic variables, activities of daily living, the disease that was the main cause of the disability, medical treatment, the feasibility of continuing family care, and some housing conditions were collected in December 1983 by interview during home visits. Deaths were checked for each year for five years. SUBJECTS--Altogether 423 people aged 65 years or more living at home in Yao City who were disabled and housebound for at least three months were studied. MEASUREMENTS AND MAIN RESULTS--Life table analysis and multivariate logistic regression analysis were done. The cumulative survival rates of old people with good housing conditions were higher than those with poor housing conditions in each group stratified by age, sex, or the activities of daily living level. The odds ratio for poor housing conditions compared with good housing conditions for five year mortality remained highly significant after adjustment for potential confounding factors including age, sex, and the activities of daily living level by logistic regression analysis. CONCLUSIONS--The mortality of frail elderly people living at home is affected by housing conditions. Programmes to improve housing conditions of the disabled are important for home care of the elderly.